THE BEGINNING OF TUROR RISQULOV'S POLITICAL ACTIVITY AND HIS ROLE IN THE POLITICAL PROCESSES OF THE COUNTRY (Scientific journal of the Fergana State University, 2025)
This article examines the political activity of Turor Risqulov, a participant in the struggle for the local population of Turkestan to gain their political rights, as well as the social, political, and economic conditions and changes in cultural life during the period of autonomy in Turkestan. It highlights Turor Risqulov's role in the political processes of the country and his social activities. Additionally, the article discusses the activities of the prominent state and public figure Turar Risqulov at the beginning of the 20th century. Today, books are being published in our Republic dedicated to the memory of the victims of political repression, and memorials have been established in honor of those who were unjustly killed. Historical justice is being restored in this way, and scholars are studying the creative legacy of those who suffered repression. Our task is to understand once again the tragic fate of the repressed leaders and to incorporate their creative legacy into national history, as discussed in the article.